Development of square wave inverter using DC/DC boost converter - M. Z. Aihsan; N. I. Ahmad; W. A. Mustafa; N. A. Rahman; J. A. Soo (Institute of Advanced Engineering and Science, 2019)
This paper proposes an alternative topology of an inverter to the existing topologies available in the market. A prototype is intended with the purpose of investigates the possibility of designing an inverter using two Boost Converters. This project initialized with a series of simulations using Matlab in order to determine the feasibility of the proposed topology. The next step is the design and development of the proposed prototype where suitable electronics components are chosen based on the simulation result. A PIC microcontroller is used to control the proposed prototype where a control scheme is created based on the programming in the microcontroller. The performance of the proposed prototype has been verified to be optimum by several practical testing using different values of capacitor, inductor and duty cycle. Lastly, data and analysis are presented in a proper mannered way. In the end, this project intends to produce stepped-up square wave output voltage waveform by proper controlling of two Boost Converters.